Pengaruh Pengawasan Terhadap Disiplin Kerja Pegawai Di Badan Penyelenggaraan Jaminan Sosial Ketenagakerjaan Kabupaten Luwu Utara - Ruwaeda, Ruwaeda; Burhanuddin, Burhanuddin; Parawu, Hafiz Elfiansyah (Universitas Muhammadiyah Makassar, 2021)
This study purposed to determine the effect of supervision on employee work discipline in the organization of labor social security in North Luwu Regency, while the research method used a qualitative method with the type of survey research and data collection techniques used observation and questionnaire.The population were all employees in the office of the organization of labor social security in North Luwu Regency as many as 61 people in addition sampling technique was saturated sampling techniques.The results showed that supervision was a process of observation and implementation of all activities of the organization to ensure that all work that was being carried out is in accordance with the plans that had been determined, while the monitoring variables could have a positive influence on employee work discipline, thus the results of the study indicated the effect of supervision on employee work discipline in the organization of labor social security in North Luwu Regency.